Implementation Mentoring, Training, Counselling, Coaching, Certification on Employee Performance - Yuni Pratikno; Supardi; Kamsariaty; Azmieti Kurnia Sinta; Oki Nandang Priyatmoko (East Asian Journal of Multidisciplinary Research, 2023)
The purpose of this scientific article is to see the implementation of the variables in this article whether it has been implemented with research results and look for supporting literature for the results of this literature research. By reviewing the literature pertinent to this research variable, qualitative techniques are used in this methodology for writing research papers. Theoretical analysis, analysis of the relationships between variables in books and journals acquired both offline and online from Mendeley, Google Scholar, and other online media. The implementation of mentoring, training, counseling, coaching, certification, on employee performance has many existing articles and uses only in the elaboration of the results above as reinforcement found by the research team who are close to the object of research in the cargo object, there has not been a maximum of representatives who state the results with the object of cargo institutions, but other fields.